THE EFFECT OF SERVICE QUALITY ON EMPLOYEE PERFORMANCE AT PT BOSOWA BERLIAN MOTOR MAKASSAR - Muh. Asdar; Muhammad Ismail; Asriyani Amrullah (Journal of Business Issues, 2023)
The Influence of Service Quality on Employee Performance at PT Bosowa Berlian Motor Makassar, supervised by Prof. Dr. H. Muh. Asdar, SE., M.Si. and Dr. Muhammad Ismail, SE., M.Si The purpose of this study was to determine and analyze the effect of service quality on employee performance at PT Bosowa Berlian Motor Makassar. The object of research is PT. Bosowa Berlian Motor Makassar. The method used is descriptive analysis and multiple linear analysis. The data collection technique in this study is a questionnaire with Multiple Linear Regression Analysis with the help of SPSS 24 software. The results of this study indicate that the better the quality of the company's service to customers, the higher the employee's performance.